Pengelolaan dan Desain Pewadahan Sampah Rumah Tangga di Kecamatan Tulangan Kabupaten Sidoarjo - Aulia Putri Agnimaya; Naufal Naufal Alesandry; Moh Hasan Haibatul Islam; Denny Oktavina Radianto (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
The background of this research is the lack of education in processing household waste in Tulangan District, Sidoarjo Regency, East Java Province which causes an increase in the rate of waste generation. Therefore, this requires good waste management. This study aims to determine the characteristics of the generated household waste. In this study, it was carried out for 8 consecutive days, by collecting household waste produced every day then weighed and divided by the total number of residents of the house. From the results of research that has been carried out for 8 consecutive days in Tulangan District, the average value of generation is 0.089 kg/hari.org, with the highest value obtained on the 7th day of 0.103 kg/hari.org caused by the consumption of residents. the house on that day was high, so that a lot of waste was generated. The value of waste generated fluctuates because it is influenced by the amount of waste produced every day. So that the design of the container used is 25 40 65 cm which is able to accommodate 61666.67 cm3 of garbage. So it can be concluded if the number of members in one family will affect the rate of waste generated. Therefore, the rate of waste generation is directly proportional to the number of residents in the house.